Locus of control, personality temperaments, and coping strategies of marine transportation students - Fernandez, Riza M.; Magallanes, Celo I. (Technium Social Sciences Journal, 2022)
The globalization of the shipping industry necessitates improving maritime students’ ability to operate under pressure. This descriptive-comparative-correlational study aims to determine 239 marine students’ locus of control, personality temperaments, and stress-coping strategies. It examines correlations among the aforementioned variables, and differences in coping in terms of year level, family structure, religion, locus of control (LOC) and temperament. The findings indicate that there is a plenitude of externals and phlegmatics among maritime students. They used coping strategies moderately across all three coping categories, namely avoidance, emotion-oriented, and task-oriented approaches, which is most preferred. Family structure, religion, and LOC do not affect their coping abilities. Choleric students coped better than sanguine and melancholic students; second-year students coped better than first-year students. Moreover, there is a link between temperament and coping, but not between temperament and LOC, nor between LOC and coping. As for externals, students would tend to believe that life circumstances or outcomes in school or elsewhere are influenced by external forces. As restrained, and sensitive phlegmatics, suppressing feelings of stress leads to more susceptibility to physical and mental stress, requiring effective coping techniques. Thus, recognizing and understanding their locus of control and temperaments will help them cope with stress more successfully.